2010
DOI: 10.1037/a0018689
|View full text |Cite
|
Sign up to set email alerts
|

Invisible expressions evoke core impressions.

Abstract: Participants viewed "hybrid" faces that showed a facial expression (anger, fear, happiness, or sadness) only in the lowest spatial frequency (1-6 cycles/image), which was blended with the same face's neutral expression in the rest of the bandwidth (7-128 cycles/image). Participants rated the portrayed persons (compared to neutral images) as "friendly" when the lowest spatial frequencies showed a positive expression and "unfriendly" when the lowest spatial frequencies showed negative expressions. In contrast, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 103 publications
6
58
3
Order By: Relevance
“…The present findings are a successful replication of the original findings of Laeng et al (2010; see also Leknes et al, 2013) regarding changes in social judgments that occur unconsciously as an effect of the low-spatial frequency information that is embedded or “hidden” within the hybrid face stimuli. The pupillary responses also revealed a consistent pattern, where the negative low-passed expressions caused the largest changes in pupillary dilations, with fear and anger causing the largest responses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present findings are a successful replication of the original findings of Laeng et al (2010; see also Leknes et al, 2013) regarding changes in social judgments that occur unconsciously as an effect of the low-spatial frequency information that is embedded or “hidden” within the hybrid face stimuli. The pupillary responses also revealed a consistent pattern, where the negative low-passed expressions caused the largest changes in pupillary dilations, with fear and anger causing the largest responses.…”
Section: Discussionsupporting
confidence: 89%
“…According to a large-scale validation study of the Karolinska Directed Emotional Faces, this included images of 20 male and 20 female models that displayed a neutral expression as well as four emotional expressions (anger, fear, happiness, and sadness). Hybrid faces were created using MatLab® software, according to a method described in Laeng and colleagues (2010) so that emotional facial expressions (anger, fear, happiness, and sadness) were presented only in low spatial frequency (<6 cycles/image) and embedded within neutral facial images of the same model shown in the rest of the bandwidth (>24 cycles/image). This cycles/image of the low-pass versions was chosen as the amygdala has been shown to respond to low spatial frequencies of <6 cycles/image but not to >24 cycles/image (Vuilleumier et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some of the most relevant preferences from an evolutionary viewpoint may occur unconsciously and when made aware they may be subjected to revision or ‘editing’ and possibly lead to less spontaneous responses and a change towards more socially accepted choices [35]. Several psychological studies have revealed that stimuli processed unconsciously can activate a broad variety of processes [52], as shown for example by research on subliminal perception of emotional expression [53], [54], [55] as well as of attractiveness [56], [57]. In addition, “mere exposure” at the subliminal level [58] can produce significant changes in the affective responses to the unconsciously processed stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is also accumulating evidence that at least unaware discrimination of facial emotional expression could also be carried out along the SC projection (cf. Hess, Reginald, Grammer, & Kleck, 2009;Laeng et al, 2010). Therefore, the degree to which the SC is involved during subliminal face processing might vary with the task.…”
Section: Discussionmentioning
confidence: 99%